2013
DOI: 10.1080/17458080.2011.607192
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel derived nickel-doped TiO2films as wear protection coatings

Abstract: Thin films of pure and Ni-doped TiO 2 were prepared on a glass substrate by sol-gel and spincoating process from specially formulated ethanol sols. The morphologies of the films surface were observed with atomic force microscope (AFM). The tribological properties of the obtained thin films sliding against steel ball were evaluated on a one-way reciprocating friction tester. AFM results show that by the addition of the Ni in TiO 2 , smooth surfaces were obtained. As a result, the Ni-doped TiO 2 films exhibit be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Metal oxide co-catalysts are typically deposited on the photocatalyst surface by sol-gel processes or via the use of surfactants. [18][19][20][21][22][23][24][25] These methods allow for a certain degree of control over the size and shape of the co-catalytic species; 19 however, they are oen limited when one-pot synthesis is desired. Wet impregnation routes, on the other hand, are simple and costeffective: for example, by using metal salt impregnation followed by thermal decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Metal oxide co-catalysts are typically deposited on the photocatalyst surface by sol-gel processes or via the use of surfactants. [18][19][20][21][22][23][24][25] These methods allow for a certain degree of control over the size and shape of the co-catalytic species; 19 however, they are oen limited when one-pot synthesis is desired. Wet impregnation routes, on the other hand, are simple and costeffective: for example, by using metal salt impregnation followed by thermal decomposition.…”
Section: Introductionmentioning
confidence: 99%
“…Nofz et al [11] mentioned that the substrate surface pretreatment modifies the integrity, homogeneity and adhesion of the coating, also pointing out that the coating thickness and depth of valleys intervene in the formation of local defects in the coating. Many authors have reported that higher roughness could be responsible for a negative response in the corrosion [24][25][26] and wear [27][28][29][30] behavior. However, in the current study, this negative response in tribocorrosion conditions was not observed and could be subject to further investigations using different coating formulations.…”
mentioning
confidence: 99%